Evolution Of Myrmecophytism In Western Malesian Macaranga (Euphorbiaceae) - Davies, Stuart J.; Lum, Shawn K.Y.; Chan, R.; Wang, L.K. (Wiley-Blackwell, 2001)
Plants inhabited by ants (myrmecophytes) have evolved in a diversity of tropical plant lineages. Macaranga includes approximately 300 paleotropical tree species; in western Malesia there are 26 myrmecophytic species that vary in morphological specializations for ant association. The origin and diversification of myrmecophytism in Macaranga was investigated using phylogenetic analyses of morphological and nuclear ITS DNA characters and studies of character evolution. Despite low ITS variation, the combined analysis resulted in a well-supported hypothesis of relationships. Mapping myrmecophytism on all most parsimonious trees resulting from the combined analysis indicated that the trait evolved independently between two and four times and was lost between one and three times (five changes). This hypothesis was robust when tested against trees constrained to have three or fewer evolutionary transformations, although increased taxon sampling for the ITS analysis is required to confirm this. Mapping morphological traits on the phylogeny indicated that myrmecophytism was not homologous among lineages; each independent origin involved a suite of different specializations for ant-plant association. There was no evidence that myrmecophytic traits underwent sequential change through evolution; self-hollowing domatia evolved independently from ant-excavated domatia, and different food-body production types evolved in different lineages. The multiple origins of myrmecophytism in Macaranga were restricted to one small, exclusively western Malesian lineage of an otherwise large and nonmyrmecophytic genus. Although the evolution of aggregated food-body production and the formation of domatia coincided with the evolution of myrmecophytism in all cases, several morphological, ecological, and biogeographic factors appear to have facilitated and constrained this radiation of ant-plants.